The Effect of Therapeutic Communication on the Intensity of Labor Pain in Active Phase I at Cengkareng Hospital - Lia Idealistiana; Trias Ayu Nugraheny (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: A study of birth mothers in England showed that 93.5% of women described severe or unbearable pain. Pain that cannot be handled alone will result in anxiety and stress. Anxiety can cause labor to go slow. Stress increases catecholamine and interferes with the release of oxytocin resulting in decreased blood flow to the uterus resulting in acidosis and hypoxia in the fetus. For mothers giving birth, it can reduce uterine contractions, so that labor will take longer. The gate control theory states that many factors influence an individual's perception of pain intensity, and some of these factors are psychological, not physiological. One of the factors that can be done is that midwives can provide mental support by providing good communication to mothers during labor, which is known as Therapeutic Communication. Methods: This research employs a Quasy Experimental research design with a Pretest-Posttest Control Group Design. The sampling technique used is purposive sampling, with a total sample size of 44 respondents. The T-Test is used to process data. Results: The results showed that there was an effect of providing therapeutic communication in reducing the intensity of labor pain in mothers in the first active phase of labor at Cengkareng Hospital with a p value <0.005, namely a p value obtained 0.000. Conclusions : There is an effect of the application of therapeutic communication on reducing labor pain in mothers in the active phase of the first stage of labour. Suggestion: It is expected to be able to apply therapeutic communication to mothers in labor.